Effects of Teaching Practice in Shaping Prospective Teachers’ Professional Identities: Comparative Analysis (Journal of Education and Educational Development, 2023)
Teaching practice gives a chance to prospective teachers to acquire professional skills, teaching methods, and different techniques of teaching. The main objectives of this study were to find out the effect of teaching practice in shaping prospective teachers’ professional identities and to compare prospective teachers and cooperative teachers’ perceptions about effects of teaching practice on professional identities. Research questions and hypothesis were formulated to achieve the main objectives of the research.  Data were collected from 45 cooperative and 80 prospective teachers selected through the purposive random technique. Data were collected through a questionnaire based on six main components of teaching practice contributing to shaping professional identities. Mean score was calculated to answer the research questions and t-test was applied to compare prospective and cooperative teachers’ perceptions. It is inferred from the findings that teaching practice plays an important role to overcome future classroom challenges. t-test results show a significant difference between prospective and cooperative teachers’ perceptions about teaching practice components. It is recommended that proper evaluation of teaching practice must be done, and prospective teachers’ feedback must be considered essential to overcome challenges of the teaching and learning process for future practices.
Keywords: Teaching Practice, Prospective Teachers, Cooperative Teachers, Professional Identities